"To keep the Senators happy, we'll go back to the old tried and true CBC shows where you can't tell the boys from the girls ." - Norris, Len (Vancouver Sun, 1966)
"To keep the Senators happy, we'll go back to the old tried and true CBC shows where you can't tell the boys from the girls ."